Global Trends in Health and Communication Research: A Bibliometric Analysis from the Scopus Database (1995–2025) - Febryanti, Ade (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The field of health and communication has experienced significant growth over the past three decades, driven by the increasing integration of digital technologies in public health and the demand for effective health information dissemination. This study aims to explore global trends in health and communication research through a bibliometric analysis of publications indexed in the Scopus database from 1995 to 2025. Using bibliometric indicators such as publication volume, authorship patterns, institutional and country collaborations, and keyword co-occurrence, this research identifies major contributors, thematic developments, and emerging research fronts in the field. The study used bibliometric analysis of 210 publications in the Scopus database from 1995 to 2025. Publication data was selected using the keyword